2011
DOI: 10.1128/aem.05087-11
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Antibiotic Resistance: Are We Born with It?

Abstract: The rapid emergence of antibiotic resistance (AR) is a major public health concern. Recent findings on the prevalence of food-borne antibiotic-resistant (ART) commensal bacteria in ready-to-consume food products suggested that daily food consumption likely serves as a major avenue for dissemination of ART bacteria from the food chain to human hosts. To properly assess the impact of various factors, including the food chain, on AR development in hosts, it is important to determine the baseline of ART bacteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
103
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 35 publications
8
103
0
2
Order By: Relevance
“…In this study, it was vital for anodic biofilm formation when AHLs were added only in inoculation process but not last over all operation time. Increased cell growth rate and generation of metabolites was also associated with improved substrate uptaking and/or metabolites excretion [8], because overexpression of key proteins is regulated by AHLs [25]. Under the regulation of AHLs in bioelctrochemical communities, bacteria can evolve to enhance the transport of endogenous electron shuttles across cell membrane to achieve more efficient extracellular electron transfer [26,27].…”
Section: Enhanced Bioelectrochemical Properties Of Mecs By Ahlsmentioning
confidence: 99%
“…In this study, it was vital for anodic biofilm formation when AHLs were added only in inoculation process but not last over all operation time. Increased cell growth rate and generation of metabolites was also associated with improved substrate uptaking and/or metabolites excretion [8], because overexpression of key proteins is regulated by AHLs [25]. Under the regulation of AHLs in bioelctrochemical communities, bacteria can evolve to enhance the transport of endogenous electron shuttles across cell membrane to achieve more efficient extracellular electron transfer [26,27].…”
Section: Enhanced Bioelectrochemical Properties Of Mecs By Ahlsmentioning
confidence: 99%
“…However, emerging data on the origins of certain AR-encoding genes, including the detection of immunity genes in antibiotic-producing organisms (1), the prevalence of ART bacteria in ready-to-consume foods (10,29,50), the colonization, persistence, and amplification of ART bacteria in host GI tracts in the absence of antibiotic exposure (27,35,54), and various AR gene stabilization, coselection, and niche fitness mechanisms (49), illustrate the complexities of the AR issue. A comprehensive understanding of the major pathways and mechanisms involved in AR emergence, amplification, persistence, and dissemination is greatly needed to achieve effective mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results from human infant studies revealed that ART bacteria established, amplified, and persisted in the human GI tract even in the absence of corresponding antibiotic exposure (27,35,54). In addition to incorporation into the chromosomal DNA, plasmid-borne genes can be retained in bacterial hosts by a number of stabilization mechanisms, such as active partitioning systems (52), the resolution system for plasmid multimers (48,52), and toxin-antitoxin (TA) systems (49).…”
mentioning
confidence: 99%
“…While commensal bacteria may be a hidden reservoir for AR genes, which can serve as an early and potentially more accurate indicator of the resistance status of the microbiota, dominant AR gene carriers vary among ecosystems, antibiotics, and even the specific AR genes within the same host or environmental microbiota. For instance, the main AR gene carriers in fermented dairy products were lactic acid bacteria and Staphylococcus sp., not E. coli (28), and while Tet r bacteria and the tetM gene pool were rapidly established in the infant gastrointestinal tract shortly after birth, no Tet r E. coli strains were recovered from the subjects during the study period (29). Feßler et al (5) reported the prevalence of multiresistant and enterotoxinogenic MRSA in food animal products.…”
mentioning
confidence: 99%
“…Meanwhile, the results also suggested an impact of human activities, environmental factors, and also possibly host specificity on AR development. More directly, Zhang et al (29) illustrated that levels of ART bacteria rose to between 10 9 and 10 10 CFU/g in the infant gut microbiota within days after birth, independent of exposure to antibiotics and intake of ART bacterium-rich conventional foods. The results illustrated a potentially significant route of AR dissemination from mother to infant and, most importantly, suggested that hosts play a critical role in the amplified circulation of ART bacteria and the AR gene pool among the environment, food, and hosts, independent of antibiotic selective pressure.…”
mentioning
confidence: 99%